A expansão rápida damaxila com Haas e a fala na fissura - Lazzari, Christiane Moraes (2007)
The aim of this study was verify the effects of rapid maxillary expansion (RME) with Haas, in speech of the pacient with transforamen cleft lip and palate. The sample consisted of 12 individuals with cleft lip and palate (CLP), being 6 boys and 6 girls, with age between 7 and 14 years, carriers of cleft lip and palate corrected with surgery. From these, 6 individuals, 3 boys and 3 girls, were submited to conventional activation ERM protocol (Group 1). The other 6 individuals, 3 boys and 3 girls, were submited to activation ERM protocol in agreement with Liou and Tsai (2005) of alternate expansions and constrictions (Group 2). The subjects were submited to fonoaudiologic evaluation of orofacial organs; nasal air capacity evaluation; perceptual analysis and spectographic evaluation of speech. The results obtained showed that RME produces changes on speech and orofacial organs in individuals with CLP. However, in some subjects, the changes did not happened in spite of RME structure changes. The increase of the nasal air capacity was statistically relevant. No statistically relevant was found between the groups in evaluations. The presente study indicated that RME produces changes on lips and tongue posture and breathing. These changes probably happen because an increase on intra-oral space, however the results showed that changes not always happen in a spontaneous way.